PERUBAHAN FISIK-SPASIAL PADA SKALA MIKRO DAN MESO KAMPUNG PULAU BELIMBING - Muhd. Arief Al Husaini (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2016)
Title: Physical-spatial Changes on Mikro and Meso Scales in Pulau Belimbing Village Pulau Belimbing is an old village in Riau province. There are some tribes live in this village such as Malay, Domo, Caniago, Piliang, and Pitopang. Village space formed based on the rule of tribe through discussion. The rule determines layout of space, fuction, and ownership. Each tribe will live in their area. Besides, village has some public area that it can used by all tribe. The rule makes the village identity differs with others village. Nowadays, the rule of village space was changing. The changes is showed on micro (house) and meso (dwelling) scale. So that, the purpose of this study is to identify the pattern of changes. This research type is desciptive qulitative in which uses historical method. The firts, finding data and fact in research area. The second, interpretation and analysis data and fact. On this research was finding several changes in micro scale such as the changing of dwelling tribe, land use and spatilal of vilage. Then the changing in micro scale such as house type becoming landed house with new material. This result can be use as restoration base of Pulau Belimbing village.